Nanostructured Catalysts for Efficient Energy Conversion: Recent Advances - Vann, Rithy; Dara, Ravi; Sok, Vann (Research of Scientia Naturalis, 2024)
The global transition towards sustainable energy sources has driven significant research into developing advanced catalytic materials that can enable efficient energy conversion processes. Nanostructured catalysts, with their unique physiochemical properties, have emerged as promising candidates to address the challenges associated with energy conversion technologies, such as low conversion efficiencies and high production costs. Understanding the recent advancements in the field of nanostructured catalysts is crucial for accelerating the development of next-generation energy conversion systems. This review article aims to provide a comprehensive overview of the recent progress in the design, synthesis, and application of nanostructured catalysts for efficient energy conversion. The study investigates the underlying principles governing the enhanced catalytic performance of nanomaterials and examines their potential impact on diverse energy conversion processes, including fuel cells, water splitting, and photocatalytic systems. The research methodology involves an extensive literature review of peer-reviewed journal articles, conference proceedings, and patent documents published within the last five years. The analysis focuses on the latest developments in the synthesis and characterization of nanostructured catalysts, as well as their performance evaluation under realistic operating conditions. The review highlights the successful implementation of various nanostructured catalyst architectures, such as nanoparticles, nanotubes, nanosheets, and core-shell structures, in enhancing the catalytic activity, selectivity, and stability for energy conversion applications. Significant advancements in the rational design of catalysts through the control of composition, morphology, and surface properties are discussed, along with their impact on improving energy conversion efficiencies and reducing production costs. The study concludes that the continued development of nanostructured catalysts holds great promise for addressing the current challenges in energy conversion technologies. The insights gained from this review can guide future research directions and facilitate the translation of nanostructured catalyst innovations into practical, large-scale energy conversion systems.